Assessment of educational needs of patients and their families after coronary artery bypass graft (CABG) surgery at discharge and one month later - Basampour; Sh. Monjamed; Z. Nikbakhtnasrabadi; A. Babaie; Gh. Moshtaghian; M. (Tehran University of Medical Sciences, 2004)
Introduction:It is necessary to give the essential educations to the patients and their families during hospitalization and after discharge. We conducted this study with objective of determining educational needs of patients undergoing CABG and their families at discharge and one month later. Materials and Methods: This research is a survey study. 60 patients and 60 members of their family who were selected by simple randomization. Data were collected by questionnaire. The questionnaire was prepared in two parts; questions about disease and demographic characteristics and specific educational needs about wound care, activity and rest, drugs, nutrition and other needs of patients and their family. The data were collected in two stages: at discharge and one month later and analyzed with SPSS software. Descriptive and inferential statistical methods (t test,  test and variance analysis) were used to analyze the data. Results: At discharge, most of the patients and their families had respectively moderate and high levels of educational needs. Both groups had moderate educational needs about rest and activity, drugs use (general educational needs), nutrition and other needs. Patients have low but their families have high educational needs about drugs use (special educational needs). At one month after discharge, most of the patients and their families had moderate educational needs in all of the mentioned categories. The t statistical test didn't show significant correlation between educational needs at discharge and one month later in patients and families. The  test showed significant differences between educational needs of the patients and their families (p=0.036) at discharge but didn't show such a difference one month after discharge (p= 0.558). Results showed a significant relationship between educational needs and level of education. Conclusion: Since most educational needs of the patients and their families concern the uses of drugs and wound care, and also most patients were unable to count their pulse, we suggest nurses pay more attention to these problems and give the essential training to the patients and their families.